GLOBAL TRENDS IN THE GREEN ECONOMY (Modern education and development, 2025)
The article is called “Global trends in green economics”  and analyzes the role and importance of green economics within modern economic systems. This article will first of all consider the basic principles and objectives of the green economy, including Sustainable Development, Environmental Protection and social justice. The article analyzes trends such as increasing demand for the green economy on a global scale, the transition to renewable energy sources, the introduction of green technologies and innovation. It also provides information on the role of the green economy in addressing climate change and environmental issues, as well as initiatives being implemented by states and corporations.